2017
DOI: 10.1016/j.exppara.2016.12.006
|View full text |Cite
|
Sign up to set email alerts
|

The Caatinga endemic Manilkara rufula possesses remarkable activity against Trichomonas vaginalis and Tritrichomonas foetus

Abstract: Tritrichomonas foetus infects the bovine urogenital tract, causing bovine trichomoniasis. Significant economic losses may occur due to infertility and abortion among cattle. Trichomonas vaginalis is the causative agent of trichomoniasis; the most common but overlooked non-viral sexually transmitted disease worldwide. Human and bovine trichomoniasis present treatment restrictions and efforts to identify new alternatives are essential. The present study evaluated the anti-trichomonads activities of seven fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…microphylla had antiproliferative properties on Trichomonas spp. The results of our study further confirmed this previous evidence ( 19 20 ).…”
Section: Discussionsupporting
confidence: 93%
“…microphylla had antiproliferative properties on Trichomonas spp. The results of our study further confirmed this previous evidence ( 19 20 ).…”
Section: Discussionsupporting
confidence: 93%
“…S1). The compound was inferred as a procyanidin dimer based on the mass spectra 35,36 . After comparison with the reference standard by HPLC, peak 4 was finally confirmed as procyanidin B2.…”
Section: Resultsmentioning
confidence: 99%
“…S1). 35,37 After comparison with the reference standard by HPLC, peak 7 was finally confirmed as epicatechin gallate.…”
Section: Resultsmentioning
confidence: 99%
“…In a study conducted byde brum Vieira et al (2017) evaluated the anti-T. vaginalis activity of 7 fractions from Manilkara rufula (Miq.) H.J.Lam leaves extracted with acetone and analyze by LC-DAD-MS/MS (liquid chromatography-diode array detectortandem mass spectrometry), MALDI-MS (matrix-assisted laser desorption/ionization-mass spectrometry), and MALDI-MS/MS.…”
mentioning
confidence: 99%